UNRAVELING THE OLD-FASHIONED MUSLIMS: Responding to The Challenges of Modernity - Syaifulloh Yazid (Jurnal Ushuluddin, 2018)
Muslims have a lot of potentials in terms of human resources (HR), natural resources (NR) and Islamic ideologies. Sadly, they are far from being established, prosperous, progressive and prosperous as they have two main challenges they must face and resolve. First, internal challenges which includes terrorism movements due to wrong understanding of Islamic teachings. Second, external challenges, such as the fear of the Europeans and the West against Islam and its adherents (Islamophobia), clash civilization stigma, and Muslim backwardness in developing science. Due to these two main challenges, it is necessary to find a solution to face and deal with them, so that the Muslims can rise above their adversity. The internal solution, for example, is to encourage them to understand the true, inclusive and interactive teachings of Islam so that they truly become a guideline and solution for any individuals and Muslims themselves. It is expected to abolish radicalism’s understanding and movement and motivate the Muslims to improve the development of science and technology. In the meantime, the external solution includes bridging communication to demonstrate the true teachings of Islam which are inclusive, merciful and interactive to eliminate Islamophobia. In addition, conducting collaborative scientific and technology-based research at international level to catch up with the modernity is also a good option